Desenvolvimento e aplicação de um equipamento para avaliação da espasticidade pelo método limiar do reflexo de estiramento tônico - Alves, Camille Marques (2019)
Spasticity is a motor disorder that affects millions of people around the world. It may originate as a sequela of a stroke, cerebral palsy, spinal cord trauma, among other factors. It is characterized by the speed dependent increase of the stretch reflex. The clinical evaluation of spasticity is of great importance in clinical practice, to get the results of rehabilitation. However, there are no standardized quantitative measures for this assessment. Thus, there is a great interest in the implementation of new methods that can adequately quantify this disorder. The Tonic Stretch Reflex Threshold (TSRT) method is very promising because it agrees with the definition of spasticity. This measure represents the articular angle at which the stretch reflex occurs. Thus, the objective of this work was to develop an equipment for the quantitative assessment of spasticity using the TSRT method. Thus, the TSRT value was obtained from the electromyographic and angular signals collected during the manual passive stretching of the affected limb, at several speeds predetermined by the developed software. The developed equipment was applied in the evaluation of spasticity of the brachial biceps, in thirteen patients. The Modified Ashworth Scale (MAS) was also used in order to correlate the two methods, since MAS is the most used in clinical practice. The equipment presented efficient results and the methodology used in the data processing was quite satisfactory, proving to be viable for application in clinical practice. However, there is a need to validate the equipment with more than one therapist. In addition, the TSRT method showed a strong correlation with the MAS, however, despite being the most used scale, it was shown that MAS it is not the best parameter to assess spasticity.